Prevalence and Risk Factors of Eimeria spp. Infection of Goats in Pempatan, Karangasem, Bali - Monica Dwi Siswanto; I Putu Cahyadi Putra; Ida Ayu Pasti Apsari; Siswanto Siswanto (Universitas Airlangga, 2026)
Background: Infection with protozoa of genus Eimeria serves as the primary etiology of caprine coccidiosis, causing significant economic losses in tropical region like Indonesia. Purpose: Determination of the prevalence and associated infection risks in goats reared in Pempatan, Karangasem, Bali, was the primary objective of this investigation. Method: Conducted from November 2025 to January 2026, this cross sectional study utilized 206 fecal samples, which were analyzed using flotation with saturated salt solution and sedimentation techniques. Interviews with farmers and local veterinarians were conducted to identify potential risk factors. Statistical analysis was performed using IBM SPSS version 26, wherein binary logistic regression was employed to analyze the relationship between risk factors and Eimeria spp. infection, with statistical significance determined via Wald’s test (p<0.05). Results: A Eimeria spp. were identified in 105 of 206 samples, yielding a prevalence of 50.97%. Significant correlations (p<0.05) were identified between infection status and factors such as age, livestock origin, and housing hygiene, while population density and general pen cleanliness showed no significant association (p>0.05). Young goats had a 2.9 times higher infection risk than adults (p = 0.001; OR = 2.898). Goats originating from outside Karangasem showed an 8.5 times higher risk than on-site bred (p = 0.004; OR = 8.476). Goats in unsanitary pens faced a 2.9 times higher risk than those in clean environments (p = 0.010; OR = 2.854). Conclusion: Characterized as moderate, the prevalence of coccidiosis among goats in Pempatan, Karangasem, Bali, necessitates urgent management interventions, including age-based grouping, stringent control of livestock movement, and the application of robust sanitation protocols for effective Eimeria spp. control.